WACANA MEDIA MASSA TENTANG KEIKUTSERTAAN UNJUK RASA KEPALA DAERAH MENOLAK KENAIKAN HARGA BBM - Karman Karman (Jurnal Studi Komunikasi dan Media, 2012)
Government’s initiative to r aise fuel price on April 1, 2012 was faced with demonstration in a numberof  regions.  In  fact,  local  goverenment  heads  mobilized  the  people  and  led  a  demonstration.  Their involvement in the demonstration made the news, evoked polemic and discourses in mass media. This writting dealt with mass media discourses regardingthat issue. This research’s used method of socialsemiotic as introduced by Halliday. That method consists of three aspects: 1) Field of discourse (what mass media’s discourse);  2)  Tenor of discourse  (persons  on the news,  their characters,  positions, and roles;  3)  Mode of discourse  (how to describe field and tenor of discourse).  This research shows that discourses on media are divided into three groups: first, discourse of law & ethics violation conducted by local government heads. Second, discourse of no-law & ethics violation. Third, discourse of no-lawviolation but ethics disrespectfullness. Discourseson media which were involved in heated fight were propalace discourse versus opponent media. Propalace discourse always referred to resources from palace’s  insiders.  Opponent  media  used  politicians, critics  as  their  resources.  Those  two  opposing groups of media harnessed language to legitimate their own argument, and delegitimate discourse in contrasting. Rencana pemerintah menaikkan harga BBM 1 April 2012disambut aksi unjuk rasa di berbagai daerah. Kepala daerah bahkan menggerakkan massa dan memimpin jalannya unjuk rasa. Keikutsertaan mereka dalam unjuk rasa menjadi pemberitaan media massa, menimbulkan polemik dan pertarungan wacana di  media  massa.  Tulisan  ini  membahas  wacana  media  massa  tentang  isu  di  atas.  Penelitian  ini menggunakan  metode  Semiotika  Sosial  Halliday.  Metode  ini  terdiri  dari  tiga  komponen:  1)  Medan Wacana  (apa  wacana  media  massa);  2)  Pelibat  Wacana  (orang-orang  yang  dicantumkan  dalam  teks berita,  sifat,  kedudukan,  dan  peranan  mereka;  3)  Sarana Wacana (cara  menggambarkan  medan,  dan pelibat wacana). Temuan penelitian menunjukkan bahwa wacana media massa terkategori menjadi 3 (tiga).  Pertama,  wacana adanya pelanggaran hukum dan etika yang dilakukan kepala daerah.  Kedua, wacana tidakadanya pelanggaran hukum dan Etika. Ketiga, wacana  tidak adanya pelanggaran hukum, namun ada pelanggaran etika. Wacana media yang sengit bertarung adalah wacana yang proistana dan media oposan. Wacana media yang proistana selalu merujuk sumberberita yang berasal dari lingkaran istana. Media  oposan  menjadikan politisi dan para pengamat sebagai sumber berita. Kedua kubu ini menggunakan  bahasa  untuk  melegitimasi  argumen  mereka  masing-masing,  dan  mendelegitimasi wacana yang berseberangan.